Lymph Node Dissection During Radical Nephro-Ureterectomy for Upper Tract Urothelial Carcinoma: A Review - Peyrottes, Arthur; Califano, Gianluigi; Ouzaïd, Idir; Lainé-Caroff, Paul; Long Depaquit, Thibaut; Hermieu, Jean-François; Xylinas, Evanguelos (Frontiers in Surgery, 2022)
Whereas lymphonodal dissection is well accepted for muscle-invasive bladder cancer management, its role is still debated during radical nephro-ureterectomy (RNU) for upper tract urothelial carcinoma (UTUC). The aim of this study was to summarize the current knowledge concerning the indication, anatomical template, prognostic and therapeutic roles of lymph node dissection (LND) performed at the time of RNU. Quality control markers such as the number of lymph node (LN) removed and lymph node density, and safety of the different surgical approaches were assessed. We performed a narrative review using the PubMed and ClinicalTrials.gov databases. We identified and analyzed articles on the practice and the role of lymph node dissection for non-metastatic UTUC. There is no clear guidelines regarding the indication of LND for UTUC but aggressive tumors should beneficiate from lymphadenectomy since lymph node invasion is a clear independent poor prognostic factor, allowing for adjuvant treatments. It seems that an extended lymphadenectomy may provide therapeutic advantages as a higher number of nodes removed may be related to the removal of undetected LNs micrometastases and the subsequent improvement in recurrence rate and cancer specific survival. Clear anatomical templates are thus needed, based on the location and the laterality of the primary tumor.